Тимур и его команда - Гайдар Аркадий Петрович (Школьная библиотека, 2011)
Экземпляры: М/а ДБ (20130318) / Инвентарный номер: 99534 / Цена: 104 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Г 14 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6